Implementasi Algoritma Gronsfeld Cipher dan Steganografi End Of File Untuk Pengamanan Data - Sedana, Kadek Vincky; Mogi, I Komang Ari; Dwidasmara, Ida Bagus Gede; Wibawa, I Gede Arta; Pramartha, Cokorda Rai Adi; Astuti, Luh Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 1 (2022): JELIKU Volume 11 No 1, August 2022, 2022)
Information is a collection of data or facts that are organized or processed in a certain way so that they have meaning for both recipients and users. Data and information are very important things to keep their security or confidentiality so that unauthorized parties cannot find out the data or information. This Data Security Application was developed using the Gronsfeld Cipher algorithm and the End Of File Steganography method. This desktop-based application was created with the aim of increasing data security on confidential information so that unauthorized parties cannot find out the contents of the data. This applicationlis expected to be a solution to prevent the theft of important information by unauthorized parties. From the test results, the developed application can receive input, process input and produce output as expected. Testing the quality of the embedded image gets an average PSNR value of 75,543 dB which can be said to be good because an image can be said to be good if it has a PSNR value above 40 dB, this also shows that the developed application can protect the data embedded in the digital image.